2013
DOI: 10.1590/s1676-06032013000300011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and biological aspects of the introduced speciesMoina macrocopa (Straus, 1820) (Crustacea, Cladocera) in the semi-arid central region of Argentina

Abstract: Moina macrocopa is common in eutrophic water bodies. Two subspecies have been described: M. macrocopa macrocopa (Straus, 1820), whose original distribution was restricted to the Old World, and M. macrocopa americanaGoulden, 1968, recorded only in North America. In 1994, the species was found in Bolivia, and in 1997 it was found in the northeast of Argentina. As the specimens belonged to M. macrocopa macrocopa in both cases, the authors suggested that it may have been introduced from the Old World by anthropoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
(37 reference statements)
0
17
0
2
Order By: Relevance
“…Colonization of New World by M . macrocopa macrocopa as a result of human-mediated introduction was documented several times by morphological taxonomists [ 63 , 95 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colonization of New World by M . macrocopa macrocopa as a result of human-mediated introduction was documented several times by morphological taxonomists [ 63 , 95 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moina species may also be considered a promising species for feeding fish larvae and fingerlings as they have a short lifespan, abundant energy storage, small size, and short embryonic stage (Sipauba-Tavares et al, 2014;Samuel, 2014). Moina macroocopa is a cladoceran mostly found in water bodies and plays a role in food chains in the aquatic environment (Iannacone and Alvarino, 2000;Vignatti et al, 2013) and, has economic importance arising from its use in aquaculture as live food for fish larval stages (Vignatti et al, 2013;Rasdi et al, 2019). Tawaratmanikul (1988) reported that Clarius batrachus, Ompok bimaculatus, Lates calcarifer and Channa striatus fish larvae show improved growth and survival for cladorans as live feed (Amornsakun et al, 2001;Budhin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Müller, 1786 and the copepod Cletocamptus in waters dominated by Cl À , whereas Sarma et al (2006) reported the prevalence of the copepods Leptodiaptomus sicilis Forbes, 1882 and Diaptomus nevadensis (Light, 1938) in waters dominated by SO 4 2À and CO 3 2À . However, information on the relationships between some aspects of the epicontinental zooplankton (diversity, density and biomass) and the ionic composition of water in southern South America (Argentina) remains relatively scarce, largely because total salinity has been considered only generally, without discriminating its components (José De Paggi and Paggi, 1998;Modenutti et al, 1998;Locascio de Mitrovich et al, 2005;Echaniz et al, 2006Echaniz et al, , 2008Echaniz et al, , 2009Echaniz et al, , 2012Vignatti et al, 2007Vignatti et al, , 2013; Battauz et al, 2013;D'Ambrosio et al, 2016). An additional complication is the frequent presence of endemic neotropical elements, particularly among cladocerans and copepods (Paggi, 1998;Menu-Marque et al, 2000;Adamowicz et al, 2004;Boxshall and Defaye, 2008;Forró et al, 2008), and little information exists that explains their patterns of temporal or biogeographic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The territory has numerous lakes, generally located in arheic basins, and these lakes, given the semi-arid nature of the region, are temporary and show large variations in level and salinity. To date, some limnological aspects of these lakes, including their zooplankton, have been studied (Echaniz et al, 2006(Echaniz et al, , 2008(Echaniz et al, , 2009(Echaniz et al, , 2012(Echaniz et al, , 2015Vignatti et al, 2007Vignatti et al, , 2012Vignatti et al, , 2013Vignatti et al, , 2016Echaniz and Vignatti, 2010, 2011Del Ponti et al, 2015); however, these studies did not consider the relationships between geographic location, anthropic influences, and the characteristics of the zooplankton community. The information is also fragmented and dispersed, and particularly scarce in terms of the relationships of the chemical composition of water, predation, the effects of human activities, and the trophic state of the lakes to the composition and density of zooplankton.…”
Section: Introductionmentioning
confidence: 99%